2013
DOI: 10.1590/s0100-72032013000300007
|View full text |Cite
|
Sign up to set email alerts
|

Depression with postpartum onset: a prospective cohort study in women undergoing elective cesarean section in Brasilia, Brazil

Abstract: Depression with postpartum onset: a prospective cohort study in women undergoing elective cesarean section in Brasilia, Brazil Abstract PURPOSE: It was to determine the prevalence of depressive symptoms in a sample of puerperal women from Brasília, Brazil, distinguishing cases with onset after delivery from those already present during pregnancy. METHODS: A prospective cohort study with convenience sampling of patients submitted to elective cesarean section at two private hospitals. As an instrument for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
1
8
0
10
Order By: Relevance
“…Studies show that women with MD identified during the postpartum period comprise a heterogeneous group (Altemus et al, 2012;Zaconeta et al, 2013). Cooper and Murray (1995) reported first-onset postpartum MDE predicted further postpartum depressive episodes but not non-postpartum depressive episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that women with MD identified during the postpartum period comprise a heterogeneous group (Altemus et al, 2012;Zaconeta et al, 2013). Cooper and Murray (1995) reported first-onset postpartum MDE predicted further postpartum depressive episodes but not non-postpartum depressive episodes.…”
Section: Discussionmentioning
confidence: 99%
“…O alto índice de 23,68% encontrado na presente investigação reforça a necessidade apontada em vários estudos, como os de Arrais et al (2014;, Bos et al (2013), Galvão et al (2015), Lara et al (2010) e Le, Perry, e Stuart (2011), sobre a importância da identificação dos sintomas iniciais que desencadeiam a DPP no puerpério, pois quanto antes se detectarem os fatores de risco e de proteção para DPP, melhor assistência poderá ser oferecida à puérpera. Desta forma, a alta prevalência de DPP encontrada reforça seu significado como problema de saúde pública, exigindo estratégias de prevenção e tratamento, como o PNP (Arrais et al, 2014;, Arrais, & Araujo, 2016 Quanto aos dados socioeconômicos não terem se associado à DPP, os achados de Alharbi e Abdulghani (2014), Bos et al (2013), Guedes et al (2011), Nunes e Phipps (2013) e Zaconeta et al (2013) e também não encontraram associação entre a idade materna e os sintomas de DPP. E apesar de eventos estressores aumentarem as chances de sintomas de DPP (Adams, Eberhard-Gran,Sandvik, & Eskild, 2012;Brummelte, Tabela 3 Teste de associação dos indicadores de fatores de risco para os sintomas de depressão pós-parto.…”
Section: Discussionunclassified
“…A.4) Fatores de proteção suporte social/relações interpessoais: Percepção de suporte social durante a gravidez (Konradt et al, 2011;Kozinszky et al, 2012); Apoio social no puerpério (Dantas, Araújo, Paulino, & Maia, 2012); e Relações sociais positivas (Bhandari et al, 2012). B.1) Fatores de risco e de proteção sociodemográficos/ contextual: Idade materna (Al Hinai, & Al Hinai, 2014;Garfield et al, 2015;Janssen, Heaman, Urquila, O'Campo, & Thiessen, 2011;Nunes, & Phipps, 2013;Wu et al, 2014); Baixo status de escolaridade (Rodríguez et al, 2013;Tian Tian et al, 2012); Desemprego ou subemprego (Al Hinai, & Al Hinai, 2014;Greinert, & Milani, 2015;Tian Tian et al, 2012); Ser solteira (Garfield et al, 2015;Rogers et al, 2013;Zaconeta, Queiroz, Amato, Motta, & Casulari, 2013). B.2) Fatores de proteção sociodemográficos/contextual: Alto status de escolaridade (Urdaneta et al, 2011).…”
Section: Fatores De Risco E Proteção Associados à Depressão Pós-partounclassified
See 1 more Smart Citation
“…In several studies, 30.6 percent, 45.7 percent and 57 percent of women will experience symptoms of depression during pregnancy [11,12]. Overall, the results of different studies in different years, the prevalence of depressive symptoms in pregnancy has shown 8-51 percent [13,14]. Depression is one the most common psychiatric disorders and mood disorders, according to the world health organization (WHO) depression is the fourth urgent health problem in the world [10], Also depression after delivery is associated with prenatal depression, The most important risk factor and predictor for depressed mood during post partum was prenatal depression and 50% of women with depression during pregnancy were depressed after delivery [15], Not only lead to complications in the mother and baby after delivery, It also led to the birth of premature infants during pregnancy, low birth weight, poor health behaviors Include: substance use (cigarettes, alcohol, and drugs) not to go for prenatal care and preeclampsia [16,17], Newborns in women experience restlessness, excessive crying, and sleep disturbance during infancy [18].…”
Section: Introductionmentioning
confidence: 98%